Analisis Yuridis terhadap Tanah Hibah yang Ditarik Kembali Menurut Perspektif Kuhper: Studi Putusan Nomor 33/Pdt.G/2019/Pn Pms) - Farah Aisyah Putri Haris; Adlin Budhiawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Grant is a voluntary gift given in a state of consciousness not under any influence simply. Then the granting of grants is also a way out of the distribution of grants in the distribution of inheritance, but it is not uncommon for this to cause problems in the future, namely grant cancellation. The case of grant cancellation exposed in the case a quo is related to the background of writing about the juridical analysis of grant cancellation regulated in the Civil Code. This research uses normative juridical research with a qualitative research type and the results of the study show that the grant cancellation case carried out in the Pematang Siantar district court is based on article 1688 concerning Grants.